Sclerosing Stromal Tumor of Ovary: A Case Report - Rana, R.; Kafle, S.U.; Jha, K.K.; Singh, M.; Gautam, P. (Birat Journal of Health Sciences, 2017)
A case of 32 year old female of pelvic pain for one month and with past history of hysterectomy performed two year back. Clinical examination revealed palpable abdominal pelvic mass. Ultrasonography showed right pelvic mass arising from right adnexa measuring 15cm x 15 cm, predominantly solid with some cystic areas. The patient was suspected of having a malignant ovarian tumor and hence operated. A histopathological diagnosis revealed sclerosing stromal tumor of ovary. Sex cord-stromal tumors account for approximately 8% of all ovarian tumor and prevalence of sclerosing stromal tumor of ovary is 1.5% to 6% .This rare neoplasm is not always possible to predict pre-operatively on the basis of clinical and radiological findings. Histologically, it is characterized by several unique features including pseudolobulation, sclerosis, and prominent vascularity. Sclerosing stromal tumor is rare but possibility of this tumor should be considered in young patients with ovarian mass having the characteristic histopathological morphology. Birat Journal of Health Sciences 2016 1(1): 83-86